Nghiên cứu tạo lớp xốp trên bề mặt màng mỏng SiC, bằng phương pháp ăn mòn điện hoá - Huỳnh, Lê Văn (Vietnam Journal of Chemistry, 2016)
Porous SiC thin films doped amorphous increasingly been widely used in many fields, especially in industrial Electronics - Electronics are used as semiconductors, insulators, insulation good…. Because there SiC thin films ability to enhance and stabilize the fluorescence of the sample SiC porous, so they are doing fluorescence applications in the LED... To make porous SiC thin films doped amorphous not (i - aSiC) often use measures electrochemical corrosion. In this paper is fabricated research results porous SiC membranes doped amorphous not by means of electrochemical corrosion i – aSiC use corrosive HF solution, if more H2O2 in the corrosion solution, fluorescence results optical gain of the SiC sample will increase a hundred times or more high, the fluorescence of the sample is also stable with time. The research results are the basis for the application of science to the practical production process technology. Keywords. Porous SiC thin films, fluorescence, corrosion.